الرؤية التنويرية عند علي عبد الرازق الإسلام وأصول الحكم مثالاً - علاء الدين, غسان (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
يسعى هذا البحث إلى توضيح المقصود بمفهوم العلمانية كما فهمه علي عبد الرازق في عام 1925 والذي كان يقصد من ورائه لا إلى فصل الدين عن الدولة ولكن إلى تحييد الجانب الديني عن الدنيوي من أجل أن يخوض في مناقشة قضايا سياسية واجتماعية لا يقف الدين حجر عثرة في طريق إنجازها. وقد كانت تجربة فريدة تستحق القراءة والفهم بهدف إنتاجها في أيامنا هذه (تأيين هذه التجربة). This article will try to clarify the concept of Secularism as it had been understood by Abdul Razek in 1925. We will try to clarify that the term Secularism was understood by Abdul Razek as distinguishing between the religion affairs and the secular affairs, in order to discourse on sociopolitical matters. This attempt was a unique experience, and it deserves to be reproduced in current times.